Simulation and Optimization of Synchronizer Shift Performance based on AMESim - Yu Xiaoxia; Zhang Zhigang; Su Hong (Jixie chuandong)
In order to improve shift performance of synchronizer,the dynamic simulation model of synchronizer is established by using AMESim softwwere. The influence of three factors on shift performance of synchronizer,such as equivalent moment inertia of the input,friction coefficient of synchronous ring and the friction angle of synchronous ring are analyzed. The four evaluation indexes are proposed,which are synchronous impulse,shift work,secondary impact and shift time. The final performance evaluating indicator is established by the method of normalization. Finally,the optimal model is obtained by the method of gradual simulation,which greatly improves shift performance of transmission.